Personhood and religious change among the Saami : reviewing historical texts - Kaikkonen, Konsta (Helsingfors universitet, 2014)
In my MA -thesis I focus on studying religious history of the Saami, particularly the role religious and cultural changes play in changing attitudes towards animals and nature. I review texts written in the 17th, 19th and early 20th centuries and thus attempt to paint a picture of the consequences of Christian missionary work in nature relations among the Saami. My focus is mainly in Finnish Lapland, but have included some complimentary sources from the Russian side as well as some works that deal with Saami religion on a larger geographical scale. The sources are written in Swedish, English and German and include nine works. The focus of my study is to use various theoretical lenses in an open-minded way. In order to analyse historical texts with a critical, multidisciplinary and comprehensive way I use theories from cognitive science of religion and cultural ecology, but try to include an intracultural and interpretational views in the study as well. The metatheoretical discussion that results from my multidisciplinary view and research focused on the contexts of my source material make this work a more theory-oriented one. I have, however, tried to focus on the interplay of sources and theories in order to balance this orientation. A key focus is in finding recurrent patterns from historical texts that concern the Saami in order to shed light on changes in animal relations. My method of analysis is conctructed of systematical analysis, ethnohistory and historical ethnography combined in order to make a three-fold scheme of research. First of all I probe into the birth histories and contexts that concern my source material in order to track the biases and prejudgements of the authors. By this I intend to proceed to filter the relevant information from the irrelevant and the biased, thus naming recurrent patterns and organizing them into heuristic concepts. In the last part of my three-fold scheme of analysis I use three theories that have their basis in cognitive psychology and cultural ecology. I have chosen ...